(untitled) (Research, Society and Development, 2022)
This study aimed to identify the clinical and morphological features of cytolytic vaginosis. This is a scoping review, carried out in three databases, with the descriptors “Cytolytic vaginosis”, “Bacterial, vaginosis” and “Vaginosis”. Among the eligibility criteria, articles published in indexed journals in the health area, available online and in full text, between 2012 and 2022, which responded to the research aim, were included. Initially, 39 articles were identified, and after screening them, seven publications were selected. The results indicated that the main features of cytolytic vaginitis are increased lactobacillus, squamous cell attrition, absence of leukocytes and cytolysis. In addition, there is the presence of whitish discharge - like the discharge generated by candidiasis, a vaginal pH between 3.5 and 4.5, hyperemia and vulvovaginal burning. Regarding treatment, evidence points to the use of sodium bicarbonate and the regulation of the vaginal microbiota. We suggest the expansion of studies on the subject, especially on detection and treatment.